Efficacy of HVT-IBDV Vector Vaccine Against Recent Egyptian vvIBDV in Commercial Broiler Chickens - Sultan, Hesham; Hussein, Hussein A.; El-Razik, Alaa G. Abd; El-Balall, Sallah; Talaat, Shaima M.; Shehata , Awad A. (International Journal of Poultry Science, 2012)
The efficacy of a turkey herpesvirus (HVT-IBD) vector vaccine encoding the VP2 gene of Infectious Bursal Disease (IBD) was evaluated in comparison with classic vaccines on two commercial broiler chicken farms (A and B), with high levels of Maternal Derived Antibodies (MDA). The HVT-IBD vaccine was administrated into chickens of farm A at 1-day-old while intermediate and intermediate-plus vaccines were given at 1-and 14-day-old into chickens of farm B, respectively. An early significant seroconversion was detected at 21-day-old in chickens of farm A, while no significant serological response was detected in farm B at this time. The antibody level was significantly higher in chickens in farm A at 28-and 35-day-old. Moreover, HVT-IBD vaccine provided complete protection against recent Egyptian vvIBDV isolate. In conclusion, HVT-IBD vaccine has the ability to induce an immune response in birds with high levels of MDA and could protect against recent Egyptian vvIBDV isolates.